Delhi's land cover change in post transit era. (February 2016) - Ahmad, Sohail; Avtar, Ram; Sethi, Mahendra; Surjan, Akhilesh
Abstract: Growing urbanization and recent Mass Rapid Transit System (MRTS) play an important role in land cover change in Indian cities. However, understanding about direction and magnitude of this change is limited, especially in reference to MRTS introduction, which is required to assess sustainable urban futures. Thus, this study attempts to assess pattern of land cover change, paying special attention to the development of MRTS (both metro lines and stations) in the National Capital Territory of Delhi. Land covers are classified using Landsat images from year 2001 and 2011. In order to measure transformations in developed areas, this study employs maximum likelihood supervised classification and performs buffer analyses along the metro lines and stations. The results reveal that growth of built-up area is higher in peripheral districts, whereas relatively low along the MRTS. This study indicates that ongoing development process needs corrective measures, such as increasing built-up areas across the metro stations and lines, and planned provisioning of physical and social infrastructure in peripheral areas to induce sustainable urban development. To implement these spatial interventions, robust implementation strategies are needed. Graphical abstract: Highlights: This study maps Delhi's land cover change between 2001 and 2011. About 11% agriculture area has decreased, while 13% built-up area has increased. Built-up area is largely added in peripheral areas rather than along transits. Transit oriented development and integrated planning in peripheral areas are sought. Robust implementation strategies are required for sustainable interventions.